2008
DOI: 10.1161/strokeaha.108.519181
|View full text |Cite
|
Sign up to set email alerts
|

Use of Carotid Intima-Media Thickness to Identify Patients With Ischemic Stroke and Transient Ischemic Attack With Low Yield of Cardiovascular Sources of Embolus on Transesophageal Echocardiography

Abstract: Background and Purpose-Carotid intima-media thickness (CIMT) is associated with systemic atherosclerosis and cardioembolic conditions and predicts the risk of recurrent strokes. We sought to establish the relationship between CIMT and cardiovascular sources of embolus (CSE) on transesophageal echocardiography (TEE) and hypothesized that a noninvasive strategy of CIMT assessment and transthoracic echocardiography bubble study would identify patients with ischemic stroke or transient ischemic attack in whom TEE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(27 reference statements)
2
7
0
1
Order By: Relevance
“…Our findings support this data particularly by the absent association with IMT. The quantification of the intima-media layer in the carotid artery [34] is one of the most commonly used surrogate markers of atherosclerosis and has been shown to predict future clinical atherosclerotic complications both cerebrovascular and coronary [18,35]. Our study did not show an independent association of IMT with SHPVO, once again corroborating a lack of causality of extracranial atherosclerosis with SHPVO.…”
Section: Discussionsupporting
confidence: 74%
“…Our findings support this data particularly by the absent association with IMT. The quantification of the intima-media layer in the carotid artery [34] is one of the most commonly used surrogate markers of atherosclerosis and has been shown to predict future clinical atherosclerotic complications both cerebrovascular and coronary [18,35]. Our study did not show an independent association of IMT with SHPVO, once again corroborating a lack of causality of extracranial atherosclerosis with SHPVO.…”
Section: Discussionsupporting
confidence: 74%
“…29 Ward et al 30 showed that an increase in CIMT by 0.80 mm correlated with an enhanced risk of carotid atherosclerosis. We found that 11.7% of our study subjects had CIMT value more than 0.80 mm and 9.9% showed plaques.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] One of the most commonly used parameters for evaluating carotid atherosclerosis by using US is the IMT, which represents the quantification of the intima-media layers of the carotid artery. 17 IMT is correlated with systemic atherosclerosis and predicts the risk of recurrent strokes. [18][19][20] Recently published articles 21,22 suggested that MDCTA can evaluate the thickness of the carotid artery wall, referred to by Saba et al 21 as CAWT, and presented results indicating significant agreement between MDCTA and CD-US in the measurement of CAWT and IMT.…”
mentioning
confidence: 99%